Continental hydroclimate during the late Paleocene-early Eocene in the central Rockies: insights from sedimentological and geochemical records preserved in the greater Green River Basin, southwestern Wyoming, U.S.A. - Gao, Min; Fan, Majie; Zhuang, Guangsheng; Chiarella, Domenico (Frontiers in Earth Science, 2025)
The late Paleocene to early Eocene (LPEE, ∼59–50 Ma) greenhouse condition is the most recent geologic analogue for future climate change induced by increased atmospheric CO2 partial pressure (pCO2). Recognition of the hyperthermals and reconstruction of the continental hydroclimate and atmospheric pCO2 during this warm period are fundamental to the understanding of Earth’s surface responses to high atmospheric pCO2. Here we study paleosol morphology, bulk organic matter δ13Corg, leaf wax n-alkanes δ13Cn-alk and δDn-alk, and reconstruct mean annual precipitation (MAP) and atmospheric pCO2 from the fine-grained floodplain deposits in the greater Green River Basin, western U.S.A., to examine the hydroclimate evolution in the continental interior during the LPEE. The Paleocene-Eocene Thermal Maximum (PETM) was identified as a ∼4‰–5‰ negative carbon isotope excursion (CIE) in the bulk organic δ13Corg record and leaf wax n-alkanes δ13Cn-alk record, and a 30‰–50‰ increase in leaf wax n-alkanes δDn-alk record. Well drained green paleosols and water-logged histosols dominated the floodplain deposition during the LPEE, and poorly drained red paleosols and carbonate-rich calcisols characterized the hyperthermal. Our reconstructed MAP is generally high (800–1,500 mm) during the LPEE and does not show significant change during the PETM. Our estimated atmospheric pCO2, by integrating bulk organic δ13Corg and paleosol carbonate δ13Cc values, is generally in the range of 600–900 ppm during the early Eocene, 1–2 times higher than the preindustrial level. These records suggest that the continental hydroclimate was generally humid and warm during the LPEE, and transient drying likely happened during the PETM.